US FOREIGN POLICY AND ICONIZATION OF A TERRORIST THROUGH HOLLYWOOD FILMS: A CONTENT ANALYSIS OF AFGHAN AND IRAQ WAR IN PRE & POST 9/11 MOVIES (1995 TO 2015) - Muhammad Majid Hamid Nasir (Journal of Peace, Development and Communication, 2021)
The study is about the cinematic representation of war on terror and explores the relationship between Hollywood productions and US foreign policy. It includes 14 Hollywood productions for cinema screen regarding Afghan and Iraq war during the era of 1995 to 2015. Content analysis of selected movies is done to find out how the ‘Other’ characters are presented on screen. The observation concludes that the Hollywood has hand in gloves with Washington to propagate the state agenda throughout the world. The image of enemy on cinematic screen is shaped and reshaped following the patterns which suit the US government as obvious in the case of Afghan and Iraq war. It is also found that the terrorist Middle Eastern and Afghan Muslim characters are mostly non-uniformed, covered head, armed, veiled, wearing upper/ jackets and wear in formal dresses. Moreover, they are iconized as animalistic, uncivilized, aggressor and have no family roles. On the contrary, the ‘Other’ characters which are supportive to American army are mostly presented as un-barbaric, civilized, defender and having family roles and they are mostly uniformed. Key words: Hollywood, “Other” Characters, US foreign Policy, War on Terror, Cinematic Representation.